Taste and Sentiment: Cartographies of Afropean Affiliation in Leonora Miano's Soulfood Équatoriale (2009)1. Issue 5 (20th October 2018) - Moji, Polo B.
Abstract: Through a study of Soulfood Équatoriale (2009), a nostalgic collection of culinary short stories by Paris-based Cameroonian writer Leonora Miano (1973–), and her essay "Afropea" (Miano, Écrits pour la parole ), this article relates culinary literary form to the AfroEuropean subjectivities. Located in the emergent field of foodways, the article examines the juxtaposition "Soulfood" as a signifier of histories of Afrodiasporic dispersal and African-American culinary tradition, with "Équatoriale" denoting the author's personal trajectory from Cameroon to becoming a naturalized French citizen or AfroEuropean. Using the dual notions of taste and nostalgia to interrogate the affective multiple affiliation created by the translocation of soul food to the Francophone Afropean space, the article frames a nascent Afropean culinary culture as a site of subjectivation created by an entangled network of cultural roots and routes, which transcend cultural and linguistic borders.